2022
DOI: 10.3390/ani12202886
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Commercial Poultry Semen Extenders Modified for Cryopreservation Procedure in the Genetic Resource Program of Czech Golden Spotted Hen

Abstract: Spermatozoa cryoconservation represents an important strategy for partial in vitro or rescue programs designed for threatened livestock populations. The procedure for the semen cryopreservation of the Czech Golden Spotted Hen was proposed due to the lower fertilization rate of poultry semen compared to mammalian species. The aim of this study was to compare commercial extenders designed for liquid storage preservation with the use of a predefined cryoprotectant, and, thus, to propose an important tool for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It was reported that the lower abnormality of sperm was produced under a NaCl physiology extender of 4.5-5.5% (Hayanti et al, 2022). It was found in other studies that sperm kept at 4 ⁰C for 72 hours produced abnormality of 8-12% (Petričáková et al, 2022;Zong et al, 2023).…”
Section: Evaluation Of Semenmentioning
confidence: 84%
“…It was reported that the lower abnormality of sperm was produced under a NaCl physiology extender of 4.5-5.5% (Hayanti et al, 2022). It was found in other studies that sperm kept at 4 ⁰C for 72 hours produced abnormality of 8-12% (Petričáková et al, 2022;Zong et al, 2023).…”
Section: Evaluation Of Semenmentioning
confidence: 84%
“…PI and YPI dyes are routinely used to determine general sperm viability by flow cytometry or fluorescent microscopy in many species (Garner et al, 1986;Graham et al, 1990;Martin et al, 2004;Ortega-Ferrusola et al, 2008;Trzcińska et al, 2008;Martínez-Pastor et al, 2010;Hossain et al, 2011;García et al, 2012;Anel-López et al, 2017;Hossen et al, 2021;Vašíček et al, 2021;Buchelly Imbachí et al, 2022;Mańkowska et al, 2022;Petričáková et al, 2022;Pytlík et al, 2022) for their ability to penetrate only spermatozoa with destabilized plasma membranes (corrupted plasma membrane or early permeabilization of the plasma membrane). Live sperm cells are not stained with these dyes.…”
Section: Introductionmentioning
confidence: 99%